2021
DOI: 10.1055/a-1715-3958
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Spinous Process–Splitting Technique for Ligamentum Flavum Cyst Removal

Abstract: Background Laminotomy for lumbar stenosis is a well-defined procedure and represents a routine in every neurosurgical department. It is a common experience that the mono- or bilateral paraspinal muscles detachment together with supra and interspinous ligaments injury can lead to postoperative pain. In literature has been reported the application at the level of the lumbar spine of a minimally invasive technique defined as lumbar spinous process-splitting technique (LSPST). Methods In the current study, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…At the same time, the results also showed that the ADPS values of the redundant group were smaller than those of the non-redundant group, and this difference was statistically significant. This method of measuring the anterior and posterior diameter values to reflect the condition of nerves within the spinal canal also meets the requirements of clinical spinal decompression procedures, such as the lumbar spinous process-splitting laminectomy (LSPSL) ( 24 , 25 ) and modified LSPSL ( 26 ). Unlike traditional laminectomy procedures, these two types of surgeries involve splitting the spinous process into two halves longitudinally in order to reduce damage to ligaments while performing decompression, preserve bone attached to adjacent ligaments, and improve postoperative stability of small joints.…”
Section: Discussionmentioning
confidence: 98%
“…At the same time, the results also showed that the ADPS values of the redundant group were smaller than those of the non-redundant group, and this difference was statistically significant. This method of measuring the anterior and posterior diameter values to reflect the condition of nerves within the spinal canal also meets the requirements of clinical spinal decompression procedures, such as the lumbar spinous process-splitting laminectomy (LSPSL) ( 24 , 25 ) and modified LSPSL ( 26 ). Unlike traditional laminectomy procedures, these two types of surgeries involve splitting the spinous process into two halves longitudinally in order to reduce damage to ligaments while performing decompression, preserve bone attached to adjacent ligaments, and improve postoperative stability of small joints.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the over-the-top technique needs to be highlighted that performing a full-endoscopic decompression is a complex technique which requires advanced endoscopic skills and should only be considered for surgeons that are already familiar with this technique. The splitting technique allows for a satisfying central decompression, with minimal sparing the facet joints and the posterior neural arch, but it is far laterally to reach the foramina and which can be insufficient decompression of lateral recess ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%